"Still more things to forget, in the wiping of Henry Patenson's bottom in the Exchequer". (June 2014) - Schofield, Roger
Abstract : The final piece of parchment of the roll kept by the Lord Treasurer's Remembrancer for 16 Henry VIII, or 1524–5, contains a very strange case. Written partly in Latin and partly in English, as was the normal practice of the Court of the Exchequer, it contains a pretended report on the dispute between John Hone, a citizen and maker of candles, on the one hand, and Henry Patenson, more familiarly known as Harry Patenson, because of his physical likeness to king Henry VIII. The defendant in the Exchequer case was described as the 'Simperyng fole of london'. This case in the Exchequer court had some exceptionally well known participants, including the Second and Third Barons of the Exchequer, who were of very high rank. This article sheds new light on Sir Thomas More.